Teleworking and occupational mental health: Reflections on the implications of the COVID-19 pandemic - San Roman Lucioni, Rodrigo (2024)
Introduction: This work critically reflects on the relationships between teleworking and occupational health in the context of the COVID-19 pandemic, with special emphasis on the Latin American region. Particularly, the implications of teleworking on occupational health and burnout syndrome are analyzed. Proposition: Key concepts are outlined, the findings of studies conducted both before and after the pandemic are examined, and the advantages of teleworking are highlighted along with its limitations due to a variety of organizational issues. Arguments for discussion: Many people have been obligated to work remotely since the COVID-19 epidemic, and more research is needed to fully understand the effects of this workplace arrangement on employees' health. Conclusion: It is determined that teleworking is a tool that enhances workers’ productivity, flexibility, and autonomy. To safeguard employees, reduce psychological risk, and advance their health and wellbeing, policies are nevertheless required. More research must be conducted to determine how teleworking affects occupational health, particularly in Latin America.